Analisis Kadar Garam Aluminium pada Beberapa Merek Deodorant Stick dengan Metode Spektrofotometri Serapan Atom (SSA) - Khamidah Fajri; Fitria Susilawati; Lija Oktya Artanti (Pharmasipha : Pharmaceutical Journal of Islamic Pharmacy, 2019)
Deodorant is a product created with the goal of reducing also covering body odor especially at the armpit through work against antimicrobial organisms cause the onset of smell. Aluminum is the active substances in the deodorant that is antibacterial and capable of reducing the amount of transpiration with underarm pores to clog. The threshold for the levels of aluminum in deodorant according to BPOM is 20%. This research was conducted to analyze the levels of aluminum salts contained in the deodorant stick which has been circulating widely in the community. Deodorant stick didestruksi using aqua regia (a mixture of HCl and HNO3), conc. For 2.5 hours. Aluminum Metal absorbance was measured using atomic absorption spectrophotometry (SSA) at a specific wavelength. The results showed that the average aluminum levels on all three samples in sequence is, sample A 1123.77 mg/L, the sample B 1.714 mg/L, and sample C 1157.13 mg/l. While the rate of percent aluminum obtained in three sample test, sample A 2.25%, sample B 0.003%, and sample C 4.63%. All three sample test have fulfilled the BPOM standard requirements about the use of aluminium in deodorants,which is no more than 20%.